PENGARUH VARIAN RETURN, VOLUME PERDAGANGAN SAHAM, BID-ASK SPREAD DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM YANG TERCATAT DALAM INDEKS LQ-45 PERIODE 2016-2019 - Ovindha Gustyas; suripto suripto; M. Iqbal Harori (Jurnal Kompetitif Bisnis, 2023)
The purpose of this study is to see how much return variance, stock trading volume, bid-ask spread, and company size affect stock prices in the LQ-45 index from 2016 to 2019. Explanatory research with a quantitative approach is used in this type of study. Companies included in the LQ-45 stock index listed on the Indonesia Stock Exchange for the 2016- 2019 period make up the study's population. Purposive sampling was used in this study, with a sample size of 25 . According to the research, trading volume and company size have a partial significant on stock prices, while return variance and bid-ask spread have a negligible significant. Return variance, trading volume, bid-ask spread, and company size all have a positive and significant effect on stock prices at the same time. These findings suggest that the return variance, trading volume, bid-ask spread, and company size all contribute to the stock price.